DIGITAL CRYPTOCURRENCIES-NEW CONTEXT FOR TRANSNATIONAL TERRORIST ACTIVITIES (Annual of the Faculty of Philosophy in Skopje, 2021)
Virtual currencies including cryptocurrencies such as Bitcoin have gotten significant popularity over the past several years. The paper’s purpose is to comprehend whether terrorist organizations and terrorist groups are presently using cryptocurrencies to funding their activities and, if not, why they do not exploit such currencies. Cryptocurrencies are easy to use, secure, and if used correctly can hide identity. That would explain why increasing research reports claim that terrorists are using them to fund their actions. Is that claim true, and if so, to what extent? And are there any realworld examples to draw on? In particular, factors that tend to discourage use contain continued unpredictability in the cryptocurrency community, cooperation between international law enforcement and the intelligence community, and developments in regulation and enforcement. The question of whether terrorist organizations will use these systems is dependent on the available technology, as well as on these groups’ needs and abilities.
Keywords: DIGITAL CRYPTOCURRENCIES; TRANSNATIONAL TERRORIST ACTIVITIES; DARK WEB; TERRORIST FUNDING